SISTEM SAPAAN DALAM WAYANG KULIT - Nurhayati, Endang (Diksi, 2015)
This article is about a research study conducted to describe the system, type, and function of form of address in wayang kulit, the Javanese leather-puppet shadow play. The subject under study was a recording of such a play titled Karna Tandhing performed by Timbul Hadiprayitna as the puppet master. The research method applied was descriptive in nature. The research data were obtained by means of a listen-and-write technique and analyzed by means of contextual interpretation. The research results are as follows. 1. The system of form of address in wayang kulit consists of aspects of (1) relation between the addresser and addressee, (2) sex/gender, (3) setting (place, time, and atmosphere), (4) purpose, (5) honoring, (6) doer, vocation, or profession, (7) marriage and love, (8) mention of dwelling place, (9) religion and belief, (10) use of pronoun, (11) zero, and (12) mention of specific identity. In type, the form of address can be, among others, (1) a pronoun, (2) a proper name: a pre-adult name, an alternative name, or dasanama, (3) a title attributed due to position of authority, (4) a name others use to call one, (5) a hereditary form of address, (6) paraban "˜a name given due to intimacy', (7) poyokan "˜a derogatory or mocking name', (8) a profession, (9) a doer of an act, (10) an expression of fondness, (11) an expression of being proud of one, (12) an expression of friendship, (13) an expression of displeasure, annoyance, or anger, (14) an expression in self-introduction, (15) an expression for peprenahan/ mbasakke "˜showing how one is related to the other by blood, age, etc.', (16) an expression related to where one dwells, (17) an expression related to position of authority, (18) an expression in honoring, (19) an expression used due to marriage: adult name, husband's name, name of first child, (20) a form of address used when addressing a god, goddess, or God, (21) a form of address for the wife of a king, (22) a form of address of zero nature, (23) an expression of cursing, (24) a form of address of specific nature, (25) a noun plus mu, e, or ne, (26) a noun, (27) a noun plus ku, (28) a form of address related to religion, (29) a form of address related to kinship plus e or ne, (30) a form of address used falsely/in playacting/pretence, and (31) a form address to point one out. In function, the form of address can be (1) honorific, i.e., to honor one, (2) to call out to one, (3) to call one with an attribute, (4) mbasakke "˜to show how one is related to the other by blood, age, etc., (5) to mock the other, (6) to show intimacy/to make intimate, (7) to show one's place of origin, (8) to introduce oneself, (9) to build a certain atmosphere, (10) to be sarcastic, (11) to clarify one's identity, (12) to be used falsely in dramatization or in a play or in pretence, and (13) to make a comic effect. Keywords: form of address, wayang kulit, system, type, function